2017
DOI: 10.1016/j.cub.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Plant Stress Tolerance Requires Auxin-Sensitive Aux/IAA Transcriptional Repressors

Abstract: Summary The Aux/IAA proteins are auxin-sensitive repressors that mediate diverse physiological and developmental processes in plants [1, 2]. There are 29 Aux/IAA genes in Arabidopsis that exhibit unique but partially overlapping patterns of expression [3] (Figure S1A). Although some studies have suggested that individual Aux/IAA genes have specialized function, genetic analyses of the family have been limited by the scarcity of loss-of-function phenotypes [4]. Further, with a few exceptions, our knowledge of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(129 citation statements)
references
References 37 publications
3
113
0
3
Order By: Relevance
“…ARF6 and ARF8 (but not ARF17) retain PB1 in their structure, which makes them targets of Aux/IAA repressor proteins. Because most previous genetic studies of Aux/IAA genes focused on characterization of gain-of-function mutants and there are only a few recent characterizations of KO mutants (23,25), we attempted to identify potential Aux/IAA partners involved in the control of AR initiation in the Arabidopsis hypocotyl. Nevertheless, likely because AR formation is a quantitative trait, we identified six iaa KO mutants showing an increased number of ARs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARF6 and ARF8 (but not ARF17) retain PB1 in their structure, which makes them targets of Aux/IAA repressor proteins. Because most previous genetic studies of Aux/IAA genes focused on characterization of gain-of-function mutants and there are only a few recent characterizations of KO mutants (23,25), we attempted to identify potential Aux/IAA partners involved in the control of AR initiation in the Arabidopsis hypocotyl. Nevertheless, likely because AR formation is a quantitative trait, we identified six iaa KO mutants showing an increased number of ARs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, genetic investigations of Aux/IAA genes have been hampered by the lack of obvious phenotype in the loss-of-function mutants (22). Nevertheless, recent careful characterization of a few of the mutants identified more precise functions in primary or LR development for IAA3 or IAA8 (23,24) or in the response to environmental stresses for IAA3, IAA5, IAA6 and IAA19 (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…These two types were merged, which resulted in a total of 1,812,475 non-redundant interactions. We also compiled a list of published TF-target interactions generated by literature curation and ChIP-seq (Jin et al 2016), eY1H (Taylor-Teeples et al 2014Sparks et al 2016;Shani et al 2017), and other methods. All interactions were merged and duplicates were removed, which resulted in a set of 1,866,371 interactions.…”
Section: Tf-target Interaction and Open Chromatin Datamentioning
confidence: 99%
“…Previous studies have also identified a considerable number of binding sites from data obtained in vivo related to different environmental perturbations in plants. For example, binding sites were screened to construct regulatory networks in response to far red light (Chen et al 2014b(Chen et al , 2014a, hormone (Fan et al 2014;Song et al 2016a;Shani et al 2017) and fungal infection (Liu et al 2015) in Arabidopsis thaliana. In contrast to expression data, binding site data present direct evidences of TF-target interactions.…”
Section: Introductionmentioning
confidence: 99%
“…These peaks were annotated to the closest gene in TAIR10 (35). The Y1H derived interactions were directly downloaded from the original publications (5)(6)(7)(45)(46)(47)(48). Protein-protein interaction data were retrieved from the studies listed in Table 3 and Gene Ontology (GO) annotations were downloaded from TAIR (35) on 9 May 2017.…”
Section: Experimental Interactionsmentioning
confidence: 99%